1997
DOI: 10.1016/s1078-5884(97)80223-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-bypass quality assessment of the long saphenous vein wall with ultrasound and histology

Abstract: Pre-existing wall changes are very common in vein grafts used for bypass surgery. However, the ultrasonic characterisation of the venous wall preoperatively cannot reliably identify these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Then again, GSVs used for coronary artery bypass grafting have also some degree of pre-existing fibrotic changes in the wall. 27 The vascular endothelium has a crucial role in the regulation of vascular homeostasis by controlling coagulation, inflammatory responses, and vascular tone. Estradiol may influence the vascular reactivity 28 due to increased nitric oxide (NO) expression and increase NO production and subsequent vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Then again, GSVs used for coronary artery bypass grafting have also some degree of pre-existing fibrotic changes in the wall. 27 The vascular endothelium has a crucial role in the regulation of vascular homeostasis by controlling coagulation, inflammatory responses, and vascular tone. Estradiol may influence the vascular reactivity 28 due to increased nitric oxide (NO) expression and increase NO production and subsequent vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the IMA is a sound graft, this study focuses on the pathological role of ET-1 and receptors in abnormal vessel wall remodeling, and as such, it essentially used the IMA as an in situ model. Giannoukas and colleagues 18 have demonstrated that ultrasound evaluation and histology of the long saphenous vein do not correlate and have shown that ultrasound was only effective in detecting Ϸ10% of moderate/severe fibrosis in this vessel. This study is novel in that it additionally evaluates structural and cellular abnormalities in association with ET-1, a pathological and potential preclinical marker of atherogenesis that is well known for its association with endothelial dysfunction.…”
Section: Editorial P 1156 Clinical Perspective P 1188mentioning
confidence: 99%
“…Handling of the surgically harvested vein is a strong outcome determinant (Conte 2009;Santo et al 2013). Preimplantation histological analysis has been proposed (Giannoukas et al 1997). External sheathing and brachytherapy failed to prevent NH (Kohler et al 1989).…”
Section: Introductionmentioning
confidence: 99%